Les ancrages organisationnels, individuels et sociaux des violences hiérarchique et organisationnelle - vers une approche globale - Chantal Aurousseau (Perspectives Interdisciplinaires sur le Travail et la Santé, 2000)
After working on two research projects and acting as a consultant on numerous cases, the author suggests some guidelines to better understand the phenomenon of organizational and hierarchical violence. Based on a first collective research, a typology of violence following two axes and four scenarios of organizational settings help to name and describe the phenomenon. The author then suggests a conceptual framework inscribing the phenomenon in a comprehensive understanding. An operational definition of violence is also put to the forth and illustrated. Before reaching a conclusion, the author develops the idea of organizational, individual and social roots to violence. These roots are keys to a better understanding of why violence is more likely to emerge or build up in some organizational settings while other settings prevent its occurrence or expansion.